THE EFFECT OF THINK-PAIR-SHARE MODEL ON STUDENTS’ INTEGRATED THEMATIC LEARNING OUTCOMES IN ELEMENTARY SCHOOL - Tiara Annisa; Reinita (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article analyzes the effect of the Think Pair Share (TPS) cooperative learning model on students’ integrated thematic learning outcomes in grade IV of SD Gugus IV, Agam Regency. The research employed a quantitative approach using an experimental method with a quasi-experimental design, specifically a nonequivalent pretest–posttest control group design. The sampling technique used was cluster random sampling involving several elementary schools within Cluster IV, Agam Regency. The fourth-grade students of SDN 13 Sungai Sariak served as the experimental group, while the fourth-grade students of SDN 22 Koto Gadang served as the control group. Based on the results of hypothesis testing using a t-test, the obtained values were tcount = 3.28 and ttable = 1.68 at a significance level of 0.05. Since tcount (3.28) > ttable (1.68), it can be concluded that Ha is accepted. This indicates that the application of the Think Pair Share (TPS) cooperative learning model has a significant effect on students’ integrated thematic learning outcomes in grade IV of SD Gugus IV, Agam Regency.